Sortase-Catalyzed Initiator Attachment Enables High Yield Growth of a Stealth Polymer from the C Terminus of a Protein - Qi, Yizhi (2013)
Conventional methods for synthesizing protein/peptide–polymer conjugates, as a means to improve the pharmacological properties of therapeutic biomolecules, typically have drawbacks including low yield, non-trivial separation of conjugates from reactants, and lack of site-specificity, which results in heterogeneous products with significantly compromised bio activity. To address these limitations, the use of sortase A from Staphylococcus aureus is demonstrated to site-specifically attach an initiator solely at the C-terminus of green fluorescent protein (GFP), followed by in situ growth of a stealth polymer, poly(oligo(ethylene glycol) methyl ether methacrylate) by atom transfer radical polymerization (ATRP). Sortase-catalyzed initiator attachment proceeds with high specificity and near-complete (≈95%) product conversion. Subsequent in situ ATRP in aqueous buffer produces 1:1 stoichiometric conjugates with > 90% yield, low dispersity, and no denaturation of the protein. This approach introduces a simple and useful method for high yield synthesis of protein/peptide–polymer conjugates. [Image: see text]